Visual Language of Angling Dharma Relief at Jago Temple - Wardaya, Marina; Mudra, I Wayan; Udayana, A. A. Gde Bagus; Suardina, I Nyoman (Universitas Ciputra, 2024)
The relief panels depicting the Angling Dharma story on the Jago Temple offer a valuable resource for researchers, similar to the Kresnayana story reliefs in Prambanan. These reliefs serve as visual narratives, conveying the Angling Dharma epic. The sculptors meticulously selected key scenes from the text, translating them into captivating visuals and arranging them within individual panels. These panels, when assembled, form a cohesive narrative of the Angling Dharma story. In a modern context, this sequence of panels resembles a movie, unfolding the story through a series of images. To encompass the entirety of the narrative within the confines of the relief's surface, the sculptors employed a distinct drawing method known as the